Analysis of melting of phase change material block inserted to an open cavity - Öztop, Hakan Fehmi; Cosanay, Hakan; Selimefendigil, Fatih; Abu-Hamdeh, Nidal (Pergamon-Elsevier Science Ltd, 2022)
A numerical work has been conducted to explore the effects of opening parameters on melting of phase change material (PCM) during natural convection in a partially open enclosure. A finned heater is located on bottom wall while the remaining parts are insulated. Paraffin wax is used as PCM and two-dimensional time dependent analysis is performed by using the finite volume method for the parameters of location of opening and temperature difference. The governing parameters for the study are chosen for the range of Ra = 1.45 x 10(8) <= Ra <= Ra = 1.97 x 10(8), 0.25 <= w/H <= 0.75 and 0.25 <= c/H <= 0.75. It is found that both opening ratio and opening length are effective parameter on melting time and these can be used as control parameters for improving the energy efficiency. Also, heat transfer can be controlled by using PCM inserted block and opening parameters. Among different cases of opening ratios and locations of opening, the most favorable configuration is obtained at Ra = 1.97 x 10(8), w/H = 0.25, c/H = 0.25 while average heat transfer enhancement by about 60% is achieved. At the lowest and highest value of Rayleigh numbers, the most favorable location of the opening is obtained at c/H = 0.25 in order to have the highest reduction amount of phase completion time.
Keywords: Partially open cavity; PCM; Melting; Computational; Finned heater